1983
DOI: 10.1109/proc.1983.12698
|View full text |Cite
|
Sign up to set email alerts
|

A tomographic formulation of spotlight-mode synthetic aperture radar

Abstract: Synthetic Aperture Radar 91 7 ~m-SpOdight-mode syathetic aperhrre radar (spotfight-mode S a ) syntkizes high-resohrtion terrain maps using data gathered from multipkobseRntionangles.'LhispfperBonstbatspottight-modeSAR~ beiaterpretedasntomogmp&recorstructionpmMemaadanalyzedllsiag dgnnlrecordedateachSARf * 'oapdatismodeledasaportionof theFouriertrilmformofacentralprojeftioaoftheimagedgrolmd8n?a. RecomhuctionofnSARimagemaythenbeoccomplisbedusingakp ritholsfromCAT.'LhismodelpennitsasimplelmderstaadingofSAR i magi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
288
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 617 publications
(295 citation statements)
references
References 20 publications
4
288
1
2
Order By: Relevance
“…Specifically, the current paper examines the morphology of smear signatures for arbitrarily moving surface targets for spotlight-mode SAR, which is a radar imaging mode [32][33][34][35][36] used to maximise image resolution at the expense of area coverage rate. The current analysis presented herein applies for all different types of spotlight SAR image formation algorithms, including, but not limited to, the polar formatting algorithm (PFA), RMA and CSA.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the current paper examines the morphology of smear signatures for arbitrarily moving surface targets for spotlight-mode SAR, which is a radar imaging mode [32][33][34][35][36] used to maximise image resolution at the expense of area coverage rate. The current analysis presented herein applies for all different types of spotlight SAR image formation algorithms, including, but not limited to, the polar formatting algorithm (PFA), RMA and CSA.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic aperture radar (SAR) sensors can produce range imagery of high spatial resolution under difficult weather conditions (Munsen et al 1983; lvlunsen and Visentin, 1989) but the image data can be difficult to interpret by human observers for several reasons. First, the sensors respond over a dynamic range of five orders of magnitude, thereby demanding some type of nonlinear compression merely for an image to he represented for viewing on a typical computer monitor (sec Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Polar format processing was originally accomplished optically, where the SAR data or phase histories were recorded on a diskshaped rotating film and lenses were used for the Fourier Transform. With later developments in tomography, and eventually digital tomography, Munson et al [3], showed that under the constraint of a planar wavefront approximation, the raw data that embodies the Fourier representation of the image are samples distributed on a polar grid. However, with the move from optical systems to digital systems for recording raw phase history data, polar format processing is no longer about rotating films and 2-D Fourier Transforms with lenses, but about the need to get the data to a Cartesian grid array for efficient digital processing and image formation of the collected SAR data.…”
Section: Introductionmentioning
confidence: 99%